Two-Stage Interpretation of Changes in TEER of Intestinal Epithelial Layers Protected by Adhering Bifidobacteria During E. coli Challenges - Yuan, Lu; van der Mei, Henny C.; Busscher, Henk J.; Peterson, Brandon W. (Frontiers in Microbiology, 2020)
Mechanisms of gastrointestinal protection by probiotic bacteria against infection involve amongst others, modulation of intestinal epithelial barrier function. Trans-epithelial electrical resistance (TEER) is widely used to evaluate cellular barrier functions. Here, we developed a two-stage interpretative model of the time-dependence of the TEER of epithelial layers grown in a transwell during Escherichia coli challenges in the absence or presence of adhering bifidobacteria. E. coli adhesion in absence or presence of adhering bifidobacteria was enumerated using selective plating. After 4–8 h, E. coli challenges increased TEER to a maximum due to bacterial adhesion and increased expression of a tight-junction protein [zonula occludens-1 (ZO-1)], concurrent with a less dense layer structure, that is indicative of mild epithelial layer damage. Before the occurrence of a TEER-maximum, decreases in electrical conductance (i.e., the reciprocal TEER) did not relate with para-cellular dextran-permeability, but after occurrence of a TEER-maximum, dextran-permeability and conductance increased linearly, indicative of more severe epithelial layer damage. Within 24 h after the occurrence of a TEER maximum, TEER decreased to below the level of unchallenged epithelial layers demonstrating microscopically observable holes and apoptosis. Under probiotic protection by adhering bifidobacteria, TEER-maxima were delayed or decreased in magnitude due to later transition from mild to severe damage, but similar linear relations between conductance and dextran permeability were observed as in absence of adhering bifidobacteria. Based on the time-dependence of the TEER and the relation between conductance and dextran-permeability, it is proposed that bacterial adhesion to epithelial layers first causes mild damage, followed by more severe damage after the occurrence of a TEER-maximum. The mild damage caused by E. coli prior to the occurrence of TEER maxima was reversible upon antibiotic treatment, but the severe damage after occurrence of TEER maxima could not be reverted by antibiotic treatment. Thus, single-time TEER is interpretable in two ways, depending whether increasing to or decreasing from its maximum. Adhering bifidobacteria elongate the time-window available for antibiotic treatment to repair initial pathogen damage to intestinal epithelial layers.